SISTEM INFORMASI AKUNTANSI YANG DIAPLIKASIKAN DALAM PELAKSANAAN PENGENDALIAN PENJUALAN : Studi Kasus pada PT. Intertrend Utama - Tessalonika Nadya Herlina; Nanik Kustiningsih (LPPM Universitas Bina Bangsa, 2022)
This article describes how the structured sales systems and procedures at PT. Main Intertrend, which in the process includes all policies and procedures that have been established by company management in order to control sales, in the right amount and to the right consumers. To achieve this, the right strategy is needed to support the smoothness of the sales system and procedures in it. PT. Intertrend Utama already has a very good and correct sales accounting system. It is proven from the ability of PT. Main Intertrend in increasing quantity, quality and profit on sales. The strategy used to support a good sales process is to pay attention to payment control activities, communication and information at the beginning of negotiations with consumers and the process of monitoring the delivery and receipt of products to the user